Effectiveness of dermabrasion plus 5‐fluorouracil vs suction blister in treating vitiligo: A comparative study. Issue 2 (17th January 2021) - Asilian, Ali; Kazemipour, Samira; Mokhtari, Fatemeh; Iraji, Fariba; Shahmoradi, Zabihollah; Mohaghegh, Fatemeh; Mozafarpoor, Samaneh; Talakoub, Mahboobeh
Abstract: Vitiligo is a prevalent destructive melanocyte skin disease that negatively affects the patients' life in terms of self‐esteem. Suction blister and dermabrasion plus 5‐fluorouracil are effective treatments for vitiligo. The present study was conducted to compare the outcomes of these two techniques. The present clinical trial was conducted on 36 patients with persistent refractory vitiligo which defined as the lack of any new or progressed lesion during the previous year as well as no responding to conventional therapies of vitiligo including topical treatments and phototherapy. Individuals with two vitiligo patches, with similar baseline Vitiligo Area Severity Index (VASI) scores were randomly allocated to dermabrasion plus 5‐fluorouracil or suction blister treatments. VASI and repigmentation scores were measured and compared at the baseline, four, and 12 weeks after performing the procedures. Both of the approaches accompanied with significant improvement in both entities of VASI and repigmentation scores ( P value < .05) at the end of the study, besides the trend of VASI and repigmentation scores between the two groups revealed insignificant difference ( P > .05). The short‐term follow‐up of the patients was the limitation of this study. The present findings suggested that both surgical techniques of dermabrasion plus 5‐fluorouracil and suction blister posed acceptable outcomes within 12‐week follow‐up.